2011
DOI: 10.1186/1471-2458-11-402
|View full text |Cite
|
Sign up to set email alerts
|

The functional status and well being of people with myalgic encephalomyelitis/chronic fatigue syndrome and their carers

Abstract: BackgroundDiagnosis of myalgic encephalomyelitis/chronic fatigue syndrome or ME/CFS is largely based on clinical history, and exclusion of identifiable causes of chronic fatigue. Characterization of cases and the impact of interventions have been limited due to clinical heterogeneity and a lack of reliable biomarkers for diagnosis and outcome measures. People with ME/CFS (PWME) often report high levels of disability, which are difficult to measure objectively. The well being of family members and those who car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
95
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 31 publications
(39 reference statements)
13
95
1
3
Order By: Relevance
“…The National Institute for Health and Care Excellence (NICE) guidelines (2007) for CFS/ME in the UK concluded that this condition effects 0.2-0.4% of the population and has been shown to have a greater impact on functional status and well-being than other chronic conditions (Nacul et al, 2011). Full recovery is rare and without intervention its natural history indicates on-going functional impairment and disability (Cairns & Hotopf, 2005;Jason et al, 2011).…”
Section: Susan Pemberton and Diane Coxmentioning
confidence: 98%
“…The National Institute for Health and Care Excellence (NICE) guidelines (2007) for CFS/ME in the UK concluded that this condition effects 0.2-0.4% of the population and has been shown to have a greater impact on functional status and well-being than other chronic conditions (Nacul et al, 2011). Full recovery is rare and without intervention its natural history indicates on-going functional impairment and disability (Cairns & Hotopf, 2005;Jason et al, 2011).…”
Section: Susan Pemberton and Diane Coxmentioning
confidence: 98%
“…Compared with many other chronic diseases, patients with ME/CFS have a lower quality of life, with major implications for patients and their families and for society (2,3). Recent research suggests that ME/CFS is associated with changes in fundamental processes of energy metabolism (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…På gruppenivå har pasienter med CFS/ME betydelig lavere funksjonsnivå enn pasienter med andre kroniske sykdommer som for eksempel kreft, depresjon eller revmatoid artritt (68,69) , se figur 1. De internasjonale konsensuskriteriene, ICC,fra august 2011 foreslår følgende inndeling (70) : • Ved mild grad er aktivitetsnivået redusert med minst 50 % sammenlignet med før sykdomsdebut, dvs.…”
Section: Alvorlighetsgrad Og Funksjonsnivåunclassified